2013
DOI: 10.1063/1.4811230
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic study of spin-transfer-torque switching of a ferromagnetic cross towards multi-state spin-transfer-torque based random access memory

Abstract: We study spin-transfer-torque (STT) switching of a cross-shaped ferromagnet with unequal branches as the free layer in a magnetic tunnel junction using micromagnetic simulations. The free layer in the magnetic tunnel junction is thus designed to have four stable energy states using shape anisotropy. Switching shows distinct regions with increasing current density. Stability of the states against thermal fluctuations is considered, and the validity of the results for different dimensions and material parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This magnetization configuration is similar to the ground state of the nano-scale cross. 49 Such magnetization alignment should result in the BVMSW modes propagating along the cross arms, which were measured in spin wave transmission experiments. At higher magnetic fields, the cross magnetization saturates along the field direction.…”
Section: Resultsmentioning
confidence: 99%
“…This magnetization configuration is similar to the ground state of the nano-scale cross. 49 Such magnetization alignment should result in the BVMSW modes propagating along the cross arms, which were measured in spin wave transmission experiments. At higher magnetic fields, the cross magnetization saturates along the field direction.…”
Section: Resultsmentioning
confidence: 99%
“…New applications in varied fields such as energy storage 1 , nanoscale photonics 2 , plasmonic nanostructures 3 , multi-bit magnetic memory 4 , terabit per square inch magnetic recording 5 , and bio-nanoparticles 6, 7 require high-throughput patterning with complex shape control at the nanoscale. Shaped nanopatterns exhibit novel optical, mechanical, and morphological properties that are exploited in various ways by these emerging fields.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we study the domain structure and the magnetic switching in the Permalloy (Fe 20 Ni 80 ) nanoscale magnetic junctions with different thicknesses by using micromagnetic simulations. It is found that both the 90-and 45-domain walls can be formed between the junctions and the wire arms depending on the thickness of the device.…”
mentioning
confidence: 99%
“…18,19 Recently, it has been reported that the magnetic switching induced by the spin-transfer torque (STT) can enable the junction to work as a STT-MRAM device. 20,21 There are also reports about the spin-polarized current that can induce the junction to generate spin waves. [22][23][24] It is found that the Permalloy junction has several metastable magnetization states, which can be used to store the information.…”
mentioning
confidence: 99%
See 1 more Smart Citation